Effect of respiratory exposure to benzene, toluene, xylene and ethyl benzene on the spirometric indices in two consecutive years among the petroleum products loading workers - Ahmad Zolfaghari (طب کار, 2020)
Introduction: Benzene, toluene, xylene and ethylbenzene (BTEX) are the most important aromatic compounds in petroleum products. Due to high vapor pressure, BTEX compounds easily change to gas form and mixed with ambient air. Petroleum products loading workers are exposed to these compounds by the inhalation of BTEX compounds. The aim of this study was to evaluate the effects of respiratory BTEX exposure on lung function indicators . Materials and Methods: A cross sectional study was conducted on petroleum products loading workers in 2015 until 2016. there were process of inclusion and exclusion in working tasks. 32 people participated in this study consciously. Eighteen samples of air was gotten in the breathing zone of workers. Sampling was performed by  indivial sampling pump 222-4 model by use of activated charcoal were taken to determine the workers' exposure to benzene, toluene, xylene and ethyl benzene. Method of sampling was 1501 NIOSH.To determine and evaluate the lung function, spirometry tests were performed according to OSHA protocols. Results: The results of analysis of samples showed that the average exposure to benzene was above the occupational exposure limit and the average exposure to ethyl benzene, toluene and xylene were below the occupational exposure limit. Lung functions indices, including FVC, FEV1, FEV1 / FVC  were reduced. Conclusion: The results showed that exposure to BTEX compounds could affect lung function indices, and reduced Lung functions indices.